2014
DOI: 10.1024/0036-7281/a000635
|View full text |Cite
|
Sign up to set email alerts
|

Antimicrobial susceptibility of mastitis pathogens of dairy cows in Switzerland

Abstract: This study evaluates the antimicrobial resistance of pathogens cultured from 3'954 quarter milk samples from dairy cows in Switzerland. A total of 1'228 Streptococcus (Strep.) uberis, 1'107 Staphylococcus (Staph.) spp. other than Staph. aureus, 598 coliform, 490 Staph. aureus, 270 Enterococcus spp. and 213 Strep. dysgalactiae isolates were tested for susceptibility to 9 antimicrobial drugs using agar diffusion. Streptococcus uberis, Strep. dysgalactiae and Staph. aureus had the highest antimicrobial sensitivit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(10 citation statements)
references
References 16 publications
0
7
0
1
Order By: Relevance
“…Subclinical IMI caused by CNS are highly prevalent in European dairy herds (Roesch et al, 2007;Sampimon et al, 2009;Rüegsegger et al, 2014), including herds with a high bulk milk SCC (Piepers et al, 2007). With improved control of major mastitis pathogens, minor pathogens, such as CNS, are coming more into focus as causative agents of increased SCC Tomazi et al, 2015).…”
Section: Introductionmentioning
confidence: 99%
“…Subclinical IMI caused by CNS are highly prevalent in European dairy herds (Roesch et al, 2007;Sampimon et al, 2009;Rüegsegger et al, 2014), including herds with a high bulk milk SCC (Piepers et al, 2007). With improved control of major mastitis pathogens, minor pathogens, such as CNS, are coming more into focus as causative agents of increased SCC Tomazi et al, 2015).…”
Section: Introductionmentioning
confidence: 99%
“…Rüegsegger et al [14] evaluated the antimicrobial resistance of 3954 milk samples isolated from samples collected from animals with subclinical and clinical mastitis diagnoses from various regions of Switzerland between 2011 and 2013. Staphylococcus spp, 598 (15%) coliform, 490(12%) S. aureus and 270(7%) Enterococcus sp.…”
Section: Discussionmentioning
confidence: 99%
“…(2012) reporting no penicillin resistance among isolates from mixed European countries, but with 29.8% of isolates being intermediate. An earlier Swiss study found only 7.8% of 1,228 S. uberis isolates resistant to penicillin (Rüegsegger et al., 2014). As this value is also %RI, it appears as if there has been a national temporal increase in resistance over the 6–9 years between isolates were obtained in these two studies.…”
Section: Assessmentmentioning
confidence: 99%
“…In Europe, the Swiss study by Rüegsegger et al. (2014) stood out with high proportions of S. uberis and S. dysgalactiae isolates (36.2% and 39.9%, respectively) being spiramycin resistant. As for other antimicrobials, this study reported %RI, meaning data may not be comparable with those of other studies, especially as a Portuguese study found a massive 30.8% of S. uberis isolates to be spiramycin intermediate (Simoes et al., 2020).…”
Section: Assessmentmentioning
confidence: 99%